If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3 + -7x) + 5x = 27 Remove parenthesis around (3 + -7x) 3 + -7x + 5x = 27 Combine like terms: -7x + 5x = -2x 3 + -2x = 27 Solving 3 + -2x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -2x = 27 + -3 Combine like terms: 3 + -3 = 0 0 + -2x = 27 + -3 -2x = 27 + -3 Combine like terms: 27 + -3 = 24 -2x = 24 Divide each side by '-2'. x = -12 Simplifying x = -12
| 8(4x+1)=3x-9x | | 2/5x+8=17/x-13 | | 2-3x=2x+12-3x | | 3x+14x-14=2x+6 | | 2(6-4d)=25-4d | | 46=-6tx-8 | | b/3+1/8=19.24 | | 3(2x-5)+x=4(x+7)-4 | | g=5*3.14*k | | 3z+8/25+1/5=z | | e^4y=4 | | 1/2+2c=3/5 | | 7m-5n= | | 5x+3=-30+2x | | 7(z-2)=-6z-8+13z | | 50h=190-45h | | b/4+1/7=19 | | 1/4y=-5x+7 | | 3(u-1)-1=-3(-4u+6)-u | | 1/4(3x-1)=2(x-2) | | x/9x=2/3 | | 29/5=k-1/5(-10k-4) | | 4/3x=44 | | 2(x-3)=5(2x+6) | | -6(9x-8)=425 | | (16+a)+11= | | 18+2x=9x+4 | | 2(x+5)=6x+10-4x | | 5(t+3)+9=3t+(-6)+6 | | 3/2(y+2)=g | | 2/3(3x-6)=10 | | 6[3-(4+4x)]=-8+2(1-14x) |